Creating Cosmopolitan Subjects: The Role of Families and Private Schools in England. (August 2016) - Maxwell, Claire; Aggleton, Peter
This article examines the ways in which cosmopolitanism is imagined and planned for by 91 young women attending four private (elite) schools in one area of England. Despite many study participants coming from families where parents travelled internationally for business, few had a strong desire to reproduce such orientations in their own futures. Moreover, the elite schools attended placed relatively little emphasis on cosmopolitanism and transnationally mobile futures. For the few English young women doing the International Baccalaureate and/or actively considering higher education abroad, the decision to do so was driven by individual rather than family or social ambitions. Through our analysis we consider further whether cosmopolitanism is a form of (cultural) capital or a quality more embedded within the girls' habitus. The relatively ambivalent attitude to cosmopolitanism found in the study schools ties in to an ethnocentrism which sees an 'English education' as among the most prestigious in the world.